KUALITAS PELAYANAN TRANSPORTASI TRANS SEMARANG KORIDOR VI RUTE UNDIP-UNNES DI KOTA SEMARANG - Anita Rahayu; Nina Widowati (Journal of Public Policy and Management Review, 2020)
ABSTRACT Semarang City is a metropolitan city which is the capital of Central Java Province. The metropolitan city is synonymous with high vehicle volumes which results in a high level of traffic congestion at several points, to overcome the congestion problem, public transportation is needed, one of which is the Trans Semarang Bus Rapid Transit (BRT). This study shows the quality of Trans Semarang BRT services in corridor IV, because the corridor is a corridor that is specialized in passing two universities and also a corridor that passes through an extreme route. Data analysis method used in this study is to use qualitative methods by incidental sampling and purposive sampling. Data collection techniques used were observation, interviews and documentation. The location of the research is in Corridor VI. In this study, using 9 characteristics of L.A. Schumer to describe the quality of transportation services. These characteristics are Speed, Safety, Capacity, Frequency, Regularity, Comprehensiveness, Responsibility, Cost Acceptable, Comfort, and inhibiting and driving factors of service quality. Based on the research results, there are 4 characteristics that have not been fulfilled. Characteristics that have not been fulfilled are Speed, Capacity Frequency, and Comfort. The inhibiting factor that needs attention is the lack of service facilities in corridor VI.